Distributions, sources, and air-sea fluxes of nitrous oxide in Bohai Bay, China - Wang, Zhi; Gu, Ting; Wen, Yujian; Cui, XuDong; Jia, Dai; Sun, Jun (Frontiers in Marine Science, 2023)
Introduction Polluted bays are one of the critical areas for the production and emissions of marine nitrous oxide (N2O), which has a strong effect on global warming and plays a critical role in stratospheric ozone depletion. Methods In 2020, the distributions of N2O concentrations and emissions in the water column of Bohai Bay (BHB) were surveyed during two cruises. Results and discussion The average N2O concentrations were higher in summer compared to autumn, with the oversaturation of N2O in both seasons. A declining gradient of N2O was found from the Hai River and Yellow River estuarine areas to the offshore sea, particularly in summer, implying riverine input was an important source of N2O. The vertical distribution of N2O was uniform in each season owing to the vertical mixing of water columns in the offshore sea, with N2O hotspots at the bottom of the two estuaries in summer and at the surface of the Hai River estuary in autumn. Moreover, the dominant sources of dissolved N2O were analyzed. N2O in the water column was predominately produced by nitrification and coupled nitrification-denitrification on suspended particulate matter. The mixing of water masses, particularly polluted water masses from coastal input, provides high N2O to the entire area of BHB, particularly in summer. Notably, nutrient and organic matter input from the coast could also indirectly drive N2O production by stimulating microbe activities of nitrification and denitrification under the water currents. In addition, statistical analysis revealed that ammonium, dissolved oxygen, and temperature were the dominant controlling factors of N2O in BHB. The annual flux of N2O in BHB was evaluated to be 6.5 Gg, accounting for 0.15% of the global oceanic N2O emission with 0.0044% of the global ocean area. Hence, as a typical polluted bay, BHB acted as a strong N2O source to the atmosphere on a per-unit-area basis.